The Elusive Search for Accountability: Evaluating Adjudicative Tribunals - Lorne Sossin (Windsor Yearbook of Access to Justice, 2010)
Evaluating the success of adjudicative tribunals is an important but elusive undertaking. Adjudicative tribunals are created by governments and given statutory authority by legislatures for a host of reasons. These reasons may and often do include legal aspects, policy aspects and partisan aspects. While such tribunals are increasingly being asked by governments to be accountable, too often this devolves into publishing statistics on their caseload, dispositions, budgets and staffing. We are interested in a different and more basic question – are these tribunals successful? How do we know, for example, whether the remedies ordered by a tribunal actually do advance the purposes for which it was created? Can the success of an adjudicative tribunal be subject to meaningful empirical validation? While issues of evaluation and accountability cut across national and jurisdictional boundaries, the authors argue that this type of question can only be addressed empirically, by actually looking to the practice of a particular board or boards, in the context of a particular statute or statutes, and in particular jurisdictions at particular times. Such accounts can and should form the basis for comparative study. Only through comparative study can the value and limitations of particular methodologies become apparent. This study takes as its case study the role of adjudicative tribunals in the health system. The authors draw primarily from Canadian tribunal experience, though examples from other jurisdictions are used to demonstrate the potential of empirical evaluation. The authors discuss the relative dearth of empirical study in administrative law and argue that it ought to be the focus of the discussion on accountability in administrative justice.